MEMBANGUN KARAKTER PESERTA DIDIK MELALUI GREEN SCHOOL DI SMK NEGERI 2 MUARA ENIM - Kristiawan, Muhammad; Maryanti, Nova; Fitria, Happy (Graduate Program Magister Manajemen Pendidikan, 2019)
Green House is a program of character education development efforts concerned about the environment in vocational school 2 Muara Enim. The object of this research is Green House in developingconscious environment of character education. The results of the research through observation, interviews and documentation showing students in character education development efforts concerned about the environment goes well, visible from the school atmosphere that is clean, tidy, beautiful and workimg together, look learners responsible and caring in keeping the school environment. Learning activities are no longer merely excavation of knowledge but at the same time utilizing the environment as a medium of learning, school residents are also encouraged to develop efforts to improve the management and quality of the environment both inside and outside school.